Tránsitos de género identidades sexuales en la reestructuración regional fronteriza Ciudad Juárez de fin de siglo - Alfredo Limas Hernández (Estudios sobre las Culturas Contemporáneas)
An essay on sexual identities in a border town like Ciudad Juarez: A region complicated not only by its economic, political and social situation, but also its geographic situation. Beginning with a look at the formation of generic identities, the author reflects upon the multiple changes in the subjectivities situated in a social space of the northern fix)ntier of Mexico. It utilizes an appropriate methodology, constituting and relating situations of culture and gender that specify aspects of the cultural shape of the country.